REMOVAL OF PFAS FROM WASTEWATER THROUGH ADSORPTION AND SORBENT INCINERATION - Sandblad, Aston (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2022)
Per- and polyfluoroalkyl substances, PFAS, are a manufactured group of chemicals that have been found to be toxic to humans and the environment. Exposure to PFAS may include birth defects for infants as well as an increased risk of cancer. Due to PFAS exceptional traits of repelling water and oil, it has commonly been used in products such as cleaning agents, clothing, and coating for furniture. Thus, PFAS reaches the environment through deposition on landfills containing residual as well as industrial waste. Another main source of contamination is aqueous firefighting foam (AFFF) which has led to areas where military and firefighters have been practicing commonly having a high concentration of PFAS in the soil and surrounding environment. PFAS has also been found to accumulate in wastewater treatment plants. It’s partly due to its water repelling traits that PFAS has been spread efficiently over the world and has been detected in remote areas, such as Greenland. Moreover, they are persistent as they don’t naturally degrade, which has led to them being referred to as “forever chemicals”. As of today, the main products for adsorption of PFAS are activated carbon as well as ion exchange resins, with activated carbon being the most common. The drawbacks with activated carbons are that even though they have high adsorption capacity they are non-selective, meaning that it adsorbs many other particles as well as PFAS. They are also not very effective on short-chained PFAS. Ion exchange resins are considered more selective as well as better at adsorbing short-chain PFAS. Both active carbon and ion exchange resins are expensive and require regeneration, which can only be performed so many times before they have to be disposed of. The objectives of this master thesis were to test three adsorbents for PFAS, study incineration of PFAS in an environment similar to Swedish incineration plants as well as perform a cost analysis that ranges from production to management of ashes. The adsorbents tested are called Granular peat ...